Engineered Bacteria of MG1363-pMG36e-GLP-1 Attenuated Obesity-Induced by High Fat Diet in Mice - Wang, Lingfang; Chen, Tingtao; Wang, Huan; Wu, Xiaoli; Cao, Qing; Wen, Ke; Deng, Ke-Yu; Xin, Hongbo (Frontiers in Cellular and Infection Microbiology, 2021)
Background Although gut hormone glucagon-like peptide 1 (GLP-1) has been widely used for treating diabetes, the extremely short half-life greatly limits its application. The purpose of this study is to explore the effects of an engineered bacteria with expression of GLP-1 on obese mice induced by high fat diet (HFD). Methods The engineered strain of MG1363-pMG36e-GLP-1 (M-GLP-1) was constructed and its anti-obesity effects were evaluated in vivo. The bodyweight, the morphology of adipose and liver tissue, and liver function were examined. Quantitative RT-PCR and Western blot were used to measure the expressions of the genes involved in fatty acid oxidation synthesis. The intestinal microbial diversity was detected with high-throughput sequencing analysis. Results The engineered bacteria could produce GLP-1. It also significantly decreased the bodyweight and improved the glucose intolerance in the obese mice induced by HFD. Moreover, the strain also reduced the triglyceride (TG) in serum, protected liver, as well as decreased the intracellular TG in liver tissues of the obese mice. Furthermore, our results showed that the expressions of the genes including peroxisome proliferator-activated receptors α (PPARα) and its target genes were enhanced in liver tissues when mice treated with M-GLP-1. Finally, we found that the engineered strain markedly increased intestinal microbial diversity. Conclusion Our results suggested the genetically engineered bacteria that constitutively secreted GLP-1 could improve obesity and the mechanism may be related to promoting fatty acid oxidation and increasing intestinal microbial diversity of the obese mice.